Implementasi Sistem Informasi Manajemen Daerah Keuangan pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan - Desi Mariana Br. Simamora; Beby Masitho Batubara; Agung Suharyanto (Universitas Medan Area, 2022)
The Regional Management Information System (SIMDA) finance is an application program that is intended to assist local governments in managing their regional finances. This study aims to determine how the implementation of financial SIMDA version 2.7 and obstacles in implementation financial SIMDA version 2.7 in the Sub-Division of Finance BPPRD Medan city. Researchers used the theory of George C. Edward III regarding implementation, namely (communication, resources, dispositions and bureaucratic structures). This type of research is descriptive qualitative research. The sources of data in this study are the head of sub-section of finance and staff of civil servants and non civil servants. Data were collected based on data collection techniques, namely observation, interviews and documentation. The informants in the study were the Head of Sub Division of Finance and financial staff. As for the results of the study showed that the implementation of the regional management information system (SIMDA) version 2.7 in the financial sub-section of the Medan City BPPRD has gone well and the staff have also understood the operation of the SIMDA. but the problem with this implementation is the disruption of the internet network connection so that it interferes with work when inputting data.